Plant and Microbial Responses to Repeated Cu(OH)2 Nanopesticide Exposures Under Different Fertilization Levels in an Agro-Ecosystem - Simonin, Marie; Colman, Benjamin P.; Tang, Weiyi; Judy, Jonathan D.; Anderson, Steven M.; Bergemann, Christina M.; Rocca, Jennifer D.; Unrine, Jason M.; Cassar, Nicolas; Bernhardt, Emily S. (Frontiers in Microbiology, 2018)
The environmental fate and potential impacts of nanopesticides on agroecosystems under realistic agricultural conditions are poorly understood. As a result, the benefits and risks of these novel formulations compared to the conventional products are currently unclear. Here, we examined the effects of repeated realistic exposures of the Cu(OH)2 nanopesticide, Kocide 3000, on simulated agricultural pastureland in an outdoor mesocosm experiment over one year. The Kocide applications were performed alongside three different mineral fertilization levels (Ambient, Low, and High) to assess the environmental impacts of this nanopesticide under low-input or conventional farming scenarios. The effects of Kocide over time were monitored on forage biomass, plant mineral nutrient content, plant-associated non-target microorganisms (i.e. N-fixing bacteria or mycorrhizal fungi) and six soil microbial enzyme activities. We observed that three sequential Kocide applications had no negative effects on forage biomass, root mycorrhizal colonization or soil nitrogen fixation rates. In the Low and High fertilization treatments, we observed a significant increase in aboveground plant biomass after the 2nd Kocide exposure (+14% and +27%, respectively). Soil microbial enzyme activities were significantly reduced in the short-term after the first exposure (day 15) in the Ambient (-28% to -82%) and Low fertilization (-25% to -47%) but not in the High fertilization treatment. However, two months later, enzyme activities were similar across treatments and were either unresponsive or responded positively to subsequent Kocide additions. There appeared to be some long-term effects of Kocide exposure, as six months after the last Kocide exposure (day 365), both beta-glucosidase (-57% in Ambient and -40% in High fertilization) and phosphatase activities (-47% in Ambient fertilization) were significantly reduced in the mesocosms exposed to the nanopesticide. These results suggest that when used in conventional farming with high fertilization rates, Kocide applications did not lead to marked adverse effects on forage biomass production and key plant-microorganism interactions over a growing season. However, in the context of low-input organic farming for which this nanopesticide is approved, Kocide applications may have some unintended detrimental effects on microbially-mediated soil processes involved in carbon and phosphorus cycling.